Numerical and small-scale physical modelling of wave transmission by wooden fences - Dao, Hoang Tung; Hofland, Bas; Suzuki, Tomohiro; Stive, Marcel J. F.; Mai, Tri; Tuan, Le Xuan (Journal of Coastal and Hydraulic Structures, 2021)
Mangrove forests, that often act as natural coastal defences, enormously suffered due to ongoing climate change and human disturbances. Thus, it is necessary to have a countermeasure to mitigate the loss of mangroves. Wooden fences are becoming a viable nature-based solution to protect vulnerable replanted mangrove forests. However, the wooden fence's hydraulic characteristics are not yet fully understood due to the complication of branches arrangement. In the present study, a small-scale wave flume modelling of wave damping by a wooden fence was constructed using the inner branches as an inhomogeneous arrangement tested in earlier flow-resistance experiments. The physical model results indicate that the wooden fence is highly effective on wave transmission and that the effectiveness in wave reduction depends on the relative fence thickness, B/Hi. To understand the scale effect on wave transmission further, the numerical model SWASH was used with the laboratory wave data. By applying the prior experiments' drag coefficient on steady flow, the uncalibrated numerical model gave a good agreement with the wave model results, with a root-mean-square error for the total transmitted wave heights of 4.7%. After validation, potential scale effects for small scale tests were determined from scaling simulations at both full scales and the applied 1:5 model scale. These simulations were performed for a fence porosity of 0.81, and different fence thicknesses to understand scale effects between model- and full-scale. Both wave reflection and transmission at model-scale are about 5% higher than full-scale results due to the increased drag coefficient and viscous effects. The effects of fence thickness and porosity were the same in large and small scale, and much larger than the error due to scale effects. Hence testing fence efficiency at physical small scale is regarded as a useful tool, together with numerical modelling.